Inorganic salt phase change material as well as preparation method and application thereof
By forming hydrated salt eutectics by sodium sulfate and carbonate in the inorganic salt phase change material composition, the phase change temperature is adjusted, and the problem of low cooling and heat storage efficiency in the heat pump system is solved, and the energy efficiency and energy storage of the heat pump system are improved ability.
Patent Information
- Application Number
- CN202411369809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
Existing phase change materials are difficult to take into account the needs of cooling and heat storage in heat pump systems, especially in high and low temperature environments, which leads to high energy consumption and excessive electricity bills.
The inorganic salt phase change material composition, including sodium sulfate and carbonate inorganic salts, is used to form a hydrated salt eutectic system by selecting the appropriate component ratio, adjust the phase change temperature between 19.5℃ and 32.0℃, and improve the phase change enthalpy and Energy storage density, and the stability and uniformity of the phase change process are ensured through the combination of heterophase nucleating agent and homogeneous nucleating agent.
It realizes thermal energy storage and release that meets multiple working modes of the heat pump system at lower energy consumption, improves the energy efficiency of the heat pump system, and ensures effective heat storage and cooling performance under different temperature environments.
Smart Images

Figure CN119264878A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage materials, and in particular to an inorganic salt phase change material and a preparation method and application thereof. Background Art
[0002] With the development of economy, people are pursuing human comfort, especially the requirements for temperature are becoming more and more sensitive. For example, in cold or hot weather, people rely on air conditioners with heat pump systems to adjust the temperature. However, simply using air conditioners for cooling / heating is too single and causes the air conditioners to run for a long time, resulting in excessive energy consumption and electricity costs. For this reason, people think of applying phase change cold storage technology to heat pump systems, using phase change materials to undergo solid-liquid and gas-liquid phase changes to store or release thermal energy. For example, using water as a phase change material, in a high temperature environment in summer, during valley power periods, air conditioning refrigeration turns water into ice. During peak power periods, ice can be turned into water to absorb heat in the environment to lower the ambient temperature, thereby effectively alleviating the problem of valley power consumption in high temperature weather; during valley power periods, air conditioners can also be used for heating, storing heat in water. Since the phase change temperature of ice to water is generally around 0°C, water mainly stores sensible heat, and the heat energy that can be stored is limited. Moreover, the higher the temperature, the greater the heat energy loss. In low temperature environments such as winter, even if water is used to store heat during valley power periods, the heat energy it stores is limited, and it is difficult to meet the heating temperature requirements, resulting in valley power in winter being difficult to be effectively utilized. Summary of the invention
[0003] The embodiments of the present application provide an inorganic salt phase change material and a preparation method and application thereof, which can solve the problem that the phase change material of a heat pump system is difficult to take into account both cold storage and heat storage requirements.
[0004] In a first aspect, an embodiment of the present application provides an inorganic salt phase change material composition, the composition comprising the following components: 31.wt.% to 45.0wt.% of a phase change substrate, 50.0wt.% to 60.0wt.% of deionized water, 1.0wt.% to 5.0wt.% of a heterogeneous nucleating agent, 2.0wt.% to 5.0wt.% of a thickener, and 0.1wt.% to 3wt.% of a crystal form regulator;
[0005] Wherein, the phase change substrate comprises sodium sulfate and inorganic salt B, the molar ratio of the sodium sulfate to the inorganic salt B is 0.9-1.1, and the inorganic salt B comprises at least one of carbonates.
[0006] In some embodiments, based on the total weight of the composition, the composition includes the following components: 36wt.% to 39wt.% of phase change substrate, 52wt.% to 54wt.% of deionized water, 3wt.% to 4wt.% of heterogeneous nucleating agent, 2.5wt.% to 4.0wt.% of thickener, and 0.5wt.% to 1.0wt.% of crystal form regulator.
[0007] In some embodiments, based on the total weight of the composition, the weight percentage of the sodium sulfate is 21.5 wt.% to 24 wt.%, and the weight percentage of the inorganic salt B is 13 wt.% to 20 wt.%.
[0008] In some embodiments, the inorganic salt B is selected from at least one of sodium carbonate, calcium carbonate, potassium carbonate, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate.
[0009] In some embodiments, the heterogeneous nucleating agent is selected from at least one of barium sulfate, zeolite, talc, and quartz sand; and the particle size Dv50 of the heterogeneous nucleating agent ranges from 350 μm to 600 μm.
[0010] In some embodiments, the crystal form modifier is selected from at least one of sodium hexametaphosphate, ammonium sulfate, and ethylenediaminetetraacetic acid.
[0011] In some embodiments, the composition further comprises a homogeneous nucleating agent, and the weight percentage of the homogeneous nucleating agent is 1.0 wt.% to 3.0 wt.% based on the total weight of the composition;
[0012] The homogeneous nucleating agent includes at least one of sodium silicate, sodium metasilicate nonahydrate, sodium metasilicate pentahydrate, and anhydrous borax.
[0013] In some embodiments, the thickener is selected from at least one of sodium polyacrylate, polyvinyl alcohol, carrageenan, and sodium carboxymethyl cellulose.
[0014] In a second aspect, the present application provides an inorganic salt phase change material, which is obtained by mixing the components of the inorganic salt phase change material composition as described above.
[0015] In a third aspect, the present application provides a heat pump system, including an energy storage unit, wherein the energy storage unit includes:
[0016] An energy storage shell having an energy storage cavity therein;
[0017] A heat exchange tube, disposed in the energy storage chamber; and
[0018] The phase change layer includes the inorganic salt phase change material as described above. The phase change layer is filled in the energy storage cavity and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
[0019] Based on the inorganic salt phase change material and its preparation method and application in the embodiments of the present application, by selecting the content of each component in the inorganic salt phase change material composition within a suitable range, and using the two inorganic salts, sodium sulfate and inorganic salt B, in combination, sodium sulfate and deionized water can generate inorganic hydrated salt A, and inorganic salt B and deionized water can generate inorganic hydrated salt B. After the inorganic hydrated salt A and the inorganic hydrated salt B are mixed, a hydrated salt eutectic system is formed. The uniformity of the crystal form of the entire inorganic salt phase change material is good, and the phase change enthalpy can be maintained at a high level. According to the principle of the eutectic of inorganic hydrated salt A and inorganic hydrated salt B, the phase change temperature of the inorganic salt phase change material can be between 19.5°C and 32.0°C, and during the phase change process, the phase change temperature stability and phase change uniformity of the inorganic salt phase change material are good. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0021] Figure 1 A method for preparing an inorganic salt phase change material according to an embodiment of the present application;
[0022] Figure 2 This is a schematic structural diagram of a heat pump system according to an embodiment of the present application;
[0023] Figure 3 is the cooling curve of the inorganic salt phase change material of Example 2-1;
[0024] Figure 4 This is the cooling curve of the inorganic salt phase change material of Comparative Example 2-1;
[0025] Figure 5 This is a DSC test graph of the inorganic salt phase change material of Example 2-1;
[0026] Figure 6 This is the DSC test graph of the inorganic salt phase change material of Comparative Example 2-1.
[0027] Reference numerals:
[0028] 10. Heat pump system; 20. Phase change layer;
[0029] 110, energy storage shell; 200, heat exchange tube; 210, first heat exchange tube; 220, second heat exchange tube;
[0030] 100, water heater; 400, air conditioner indoor unit;
[0031] 300, heat source unit; 310, outlet end; 320, inlet end;
[0032] 500, reversing valve; 510, first reversing valve; 520, second reversing valve;
[0033] 610. Municipal water source; 620. Domestic water pipe. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] It should be noted that, in various aspects of the present application, for the same components in various aspects, the present application only describes one aspect once without repeating the description, which should not be understood by those skilled in the art as a limitation to the present application.
[0036] In the present application, unless otherwise stated, the room temperature or normal temperature refers to 25±2°C.
[0037] As mentioned above, the present application provides an inorganic salt phase change material composition, which can be used to prepare an inorganic salt phase change material. The inorganic salt phase change material can be used in a heat pump system to store heat and cold.
[0038] Specifically, the inorganic salt phase change material absorbs heat from the heat source unit during its heat storage process and stores the heat so that when the user needs heat, the inorganic salt phase change material can release heat and transfer the heat to the heat exchange medium, and the heat is transferred through the heat exchange medium for the user to use. For example, the heat pump system may include a water heater and an air-conditioning indoor unit. The inorganic salt phase change material can be used in the water heater. The inorganic salt phase change material transfers heat to the municipal water in the heat exchange tube, and heats the municipal water into domestic water with a higher temperature for the user to use; the inorganic salt phase change material can also be used in the air-conditioning indoor unit. The inorganic salt phase change material transfers heat to the air flow in the heat exchange tube, and heats the air flow into a higher temperature air flow to increase the ambient temperature of the air-conditioning indoor unit. Similarly, the inorganic salt phase change material can also store cold under the action of the heat source unit, so that when the heat source unit is used in a water heater, the inorganic salt phase change material can absorb heat and cool the municipal water into a lower temperature domestic water for users to use; and when the heat source unit is used in the air conditioner indoor unit, the inorganic salt phase change material can absorb heat and cool the airflow into a lower temperature airflow to flow out, thereby reducing the ambient temperature of the air conditioner indoor unit.
[0039] During the valley electricity period, the heat source unit can use the valley electricity for cooling or heating. When the heat source unit is heating, the inorganic salt phase change material stores heat energy, and when the heat source unit is cooling, the inorganic salt phase change material stores cold energy. In low temperature environments such as winter and frost, thermal energy is mainly needed to increase the ambient temperature, and the required thermal energy is large. Therefore, the inorganic salt phase change material needs to have a higher heat storage capacity. When the phase change temperature of the inorganic salt phase change material is low, the inorganic salt phase change material undergoes phase change at a lower temperature, and it mainly stores sensible heat, and the stored thermal energy is limited. Phase change materials such as water have a phase change temperature of 0°C, and sensible heat storage is performed above 0°C, and the stored energy is limited. Therefore, when an inorganic salt phase change material with a lower phase change temperature is selected, in a low temperature environment, it is difficult to fully utilize the valley electricity. In addition, the phase change temperature of the inorganic salt phase change material cannot be too high. When the phase change temperature of the inorganic salt phase change material is too high, a heat source unit with a higher heating temperature is required to supply heat to the inorganic salt phase change material for phase change energy storage. The higher the temperature of the heat source unit, the lower the utilization rate of the thermal energy converted by the heat source unit to the inorganic salt phase change material, resulting in relatively low energy efficiency of the entire heat pump system.
[0040] Based on this, an embodiment of the present application provides an inorganic salt phase change material with a phase change temperature of 19.5°C to 32.0°C. The inorganic salt phase change material can store heat and cold to meet the requirements of various working modes of the heat pump system.
[0041] The inorganic salt phase change material of the embodiment of the present application is prepared by mixing an inorganic salt phase change material composition, and the inorganic salt phase change material composition includes the following components:
[0042] 30.0wt.% to 45.0wt.% of phase change substrate, 50.0wt.% to 60.0wt.% of deionized water, 2.0wt.% to 4.0wt.% of heterogeneous nucleating agent, 2.0wt.% to 5.0wt.% of thickener, and 0.1wt.% to 1.5wt.% of crystal modifier; wherein the phase change substrate comprises sodium sulfate and inorganic salt B, and the molar ratio of sodium sulfate to inorganic salt B is 0.9 to 1.1; the inorganic salt B is selected from at least one of carbonates, specifically, the carbonate is selected from at least one of sodium carbonate, calcium carbonate, potassium carbonate, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate.
[0043] In the present application, inorganic salt and deionized water are the main components that undergo phase change in the inorganic salt phase change material. The inorganic salt is combined with deionized water to form an inorganic hydrated salt, and stores heat during the melting process and releases heat during the crystallization process, thereby performing phase change energy storage. The heterogeneous nucleating agent is used to provide nucleation sites for the inorganic hydrated salt so that the inorganic hydrated salt can be repeatedly melted and crystallized. The crystal form regulator is used to change the crystal shape of the inorganic hydrated salt crystal so that the inorganic salt phase change material has a suitable thermal enthalpy. The thickener can increase the overall viscosity of the inorganic salt phase change material to inhibit the phase separation of the inorganic salt phase change material, so that the inorganic salt phase change material has good stability during frequent phase changes.
[0044] Among them, when the components of the inorganic salt phase change material composition are evenly mixed, sodium sulfate and deionized water can generate inorganic hydrated salt A, and inorganic salt B and deionized water can generate inorganic hydrated salt B. The phase change temperature of the mixture formed by mixing the inorganic hydrated salt A and the inorganic hydrated salt B is the basis of the phase change temperature of the inorganic salt phase change material. The embodiment of the present application selects the content of each component in the inorganic salt phase change material composition within a suitable range, and uses sodium sulfate and inorganic salt B in combination. After the inorganic hydrated salt A and the inorganic hydrated salt B are mixed, the uniformity of the crystal form of the entire inorganic salt phase change material is good, and the phase change enthalpy of the inorganic salt phase change material can be maintained at a high level. According to the principle of the eutectic of inorganic hydrated salt A and inorganic hydrated salt B, the phase change temperature of the inorganic salt phase change material can be between 19.5°C and 32.0°C, and during the phase change process, the inorganic salt phase change material has good phase change temperature stability and good phase change uniformity.
[0045] When the weight percentage of the phase change substrate is lower than the lower limit of 30.0wt.%, the enthalpy of the inorganic salt phase change material decreases and the energy storage density is low. When the weight percentage of the phase change substrate is higher than the upper limit of 42.0wt.%, the proportion of other components decreases, and there is a risk of supercooling and phase separation. When the molar ratio of sodium sulfate to inorganic salt B is lower than the lower limit of 0.9 or lower than the upper limit of 1.1, the proportion of one of the two inorganic salts is too high, resulting in failure to form a eutectic, and the purpose of lowering the phase change temperature cannot be achieved.
[0046] In some embodiments, based on the total weight of the composition, the composition includes the following components: 36 wt.% to 39 wt.% of a phase change substrate, 52 wt.% to 54 wt.% of deionized water, 3 wt.% to 4 wt.% of a heterogeneous nucleating agent, 2.5 wt.% to 4.0 wt.% of a thickener, and 0.5 wt.% to 1.0 wt.% of a crystal form regulator. Under this composition, since the inorganic hydrated salt A and the inorganic hydrated salt B crystallize to form a hydrated salt eutectic system, and the thickener increases the viscosity of the hydrated salt eutectic system, prevents the hydrated salt eutectic system from settling, and inhibits phase separation, the heat storage performance of the system is stable and the supercooling degree is low.
[0047] In some embodiments, based on the total weight of the composition, the weight percentage of sodium sulfate is 21.5 wt.% to 24 wt.%, within this range, sodium sulfate can form a eutectic with the inorganic salt B, thereby achieving the purpose of lowering the phase transition temperature.
[0048] In some embodiments, based on the total weight of the composition, the weight percentage of inorganic salt B is 13 wt.% to 20 wt.%, within which the inorganic salt B can form a eutectic with sodium sulfate, thereby achieving the purpose of lowering the phase transition temperature. The inorganic salt B is selected from at least one of carbonates: sodium carbonate, calcium carbonate, potassium carbonate, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate.
[0049] In some embodiments, the heterogeneous nucleating agent is selected from at least one of barium sulfate (BaSO4), zeolite, talc, and quartz sand. The heterogeneous nucleating agent is a water-insoluble substance. The particle size Dv50 of the heterogeneous nucleating agent is 350μm to 600μm. Within this particle size range, the heterogeneous nucleating agent can provide nucleation sites for inorganic hydrated salt A and inorganic hydrated salt B so that inorganic hydrated salt A and inorganic hydrated salt B can crystallize, and can also solve the problem of phase change material having no crystal nucleus when the homogeneous nucleating agent fails.
[0050] In some embodiments, the composition also includes a homogeneous nucleating agent, which is soluble in water. The homogeneous nucleating agent is selected from at least one of anhydrous borax, sodium silicate, sodium metasilicate pentahydrate, and sodium metasilicate nonahydrate. The above-mentioned homogeneous nucleating agent can be well dissolved in inorganic hydrated salts, thereby reducing the energy threshold required for crystallization of the hydrated salt eutectic system, making the inorganic hydrated salt A and the inorganic hydrated salt B easier to crystallize, and can promote crystal growth to ensure the latent heat of phase change.
[0051] In some embodiments, based on the total weight of the composition, the weight percentage of the homogeneous nucleating agent is 1.0 wt.% to 3.0 wt.%, and the homogeneous nucleating agent can further improve the crystal form and degree of crystallization, and increase the thermal enthalpy per unit mass of the inorganic salt phase change material.
[0052] In some embodiments, heterogeneous nucleating agents and homogeneous nucleating agents can also be used in combination and co-exist in the inorganic salt phase change material composition. When the composition also includes a crystal form regulator, the heterogeneous nucleating agent and the homogeneous nucleating agent are used to provide crystallization sites for the inorganic hydrated salt A and the inorganic hydrated salt B, respectively, and the crystal form regulator can further improve the crystal shape, help the inorganic hydrated salt A and the inorganic hydrated salt B to form a eutectic, improve the crystallinity, and ensure that the inorganic salt phase change material has a suitable thermal enthalpy.
[0053] In some embodiments, the crystal form modifier is selected from at least one of sodium hexametaphosphate, ammonium sulfate, and ethylenediaminetetraacetic acid.
[0054] In some embodiments, the thickener is selected from at least one of sodium polyacrylate (PAAS), polyvinyl alcohol, carrageenan, and sodium carboxymethyl cellulose (CMC). The thickener can be well swelled and evenly dissolved to improve phase separation.
[0055] The present application also provides an inorganic salt phase change material, which is prepared by mixing the components of the inorganic salt phase change material composition described above.
[0056] In some embodiments, the enthalpy value per unit mass of the inorganic salt phase change material is 200 J / g to 220 J / g. The inorganic salt phase change material has good heat storage and cold storage capabilities and can store more heat energy or cold energy, thereby storing more energy during peak power periods and valley power periods, so as to perform more heat energy conversion under the corresponding working mode of the heat pump system.
[0057] In some embodiments, the supercooling degree of the inorganic salt phase change material is 0.5°C to 7°C. In the present application, when sodium sulfate and inorganic salt B are used in combination, the supercooling degree of the inorganic salt phase change material can still be maintained at a low level, the crystallization temperature of the inorganic salt phase change material is stable, and phase change energy storage is more stably performed.
[0058] In some embodiments, the solidification temperature (i.e., phase change temperature) of the inorganic salt phase change material is 19.5°C to 30.0°C, and the melting temperature of the inorganic salt phase change material is 22.5°C to 24.5°C. Below the solidification temperature, the inorganic salt phase change material solidifies, and above the melting temperature, the inorganic salt phase change material melts into a liquid state. In the temperature range between the solidification temperature and the melting temperature, the inorganic salt phase change material can absorb / release a large amount of heat within this temperature range, and can continuously provide sufficient cold source / heat source for cooling / heating.
[0059] In some embodiments, the enthalpy decay rate per unit mass of the inorganic salt phase change material after 500 cycles is ≤5%, and the inorganic salt phase change material can still maintain good heat storage capacity after multiple melting and crystallization.
[0060] The embodiment of the present application also provides a method for preparing an inorganic salt phase change material, comprising mixing the components in the inorganic salt phase change material composition as described above to prepare the inorganic salt phase change material as described above.
[0061] like Figure 1 As shown, in the embodiment of the present application, mixing the components of the inorganic salt phase change material composition includes the following steps:
[0062] Step S1, providing an inorganic salt phase change material composition, the composition comprising a phase change substrate, deionized water, a heterogeneous nucleating agent, a thickener and a crystal form regulator, the phase change substrate comprising sodium sulfate and an inorganic salt B, the molar ratio of sodium sulfate to inorganic salt B being 0.9 to 1.1; the inorganic salt B is selected from at least one of carbonates, specifically, the carbonate is selected from at least one of sodium carbonate, calcium carbonate, potassium carbonate, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate. In some embodiments, the composition further comprises a homogeneous nucleating agent.
[0063] Step S2: Mix the components in the composition to obtain a molten intermediate mixture, the temperature of the intermediate mixture being a preset temperature T0.
[0064] Step S3, subjecting the intermediate mixture to an activation treatment, the activation treatment comprising:
[0065] Step S310, cooling the intermediate mixture to a first temperature T1 to obtain a solidified first mixture;
[0066] Step S320, heat-insulating the first mixture at the first temperature T1 to obtain a second mixture;
[0067] Step S330, heating the second mixture to a second temperature T2 to obtain a molten third mixture; wherein T1 <T0≤T2;
[0068] Step S4: Stir the third mixture, and after cooling and solidification, obtain an inorganic salt phase change material.
[0069] In the embodiment of the present application, the heterogeneous nucleating agent and the homogeneous nucleating agent are activated by activation treatment to activate the heterogeneous nucleating agent and the homogeneous nucleating agent, so that the heterogeneous nucleating agent and the homogeneous nucleating agent are more evenly dispersed in the inorganic salt phase change material, and can provide crystallization sites for the inorganic hydrated salt A formed by sodium sulfate and the inorganic hydrated salt B formed by the inorganic salt B, respectively, so that the inorganic salt phase change material can have a stable solidification temperature and melting temperature. Among them, the cooling treatment is used to make the intermediate mixture crystallize and harden to obtain the first mixture in the state of hydrogel, the heat preservation treatment is used to further stabilize the crystal form of the first mixture to obtain a solidified second mixture, and the heating treatment is used to heat and melt the solidified second mixture to become a hydrogel in a flowing state. In this way, after the high and low temperature shock, the heterogeneous nucleating agent and the homogeneous nucleating agent are activated, so that the heterogeneous nucleating agent and the homogeneous nucleating agent are evenly dispersed in the inorganic salt phase change material and stabilized in a certain position by the thickener, providing a large number of sites for the nucleation and crystallization of the inorganic hydrated salt A and the inorganic hydrated salt B, ensuring the stability and sufficiency of the crystallization, further reducing the supercooling of the inorganic salt phase change material and increasing the thermal enthalpy per unit mass (i.e., the latent heat of phase change).
[0070] In step S1, the sodium sulfate, inorganic salt B, deionized water, heterogeneous nucleating agent, thickener and crystal form regulator of the composition are mixed uniformly, the sodium sulfate is combined with deionized water to form inorganic hydrated salt A, and the inorganic salt B is combined with deionized water to form inorganic hydrated salt B. In step S1, the inorganic salt phase change material composition provided includes the following components:
[0071] Phase change substrate 30.0wt.%~45.0wt.%, deionized water 50.0wt.%~60.0wt.%, heterogeneous nucleating agent 2.0wt.%~4.0wt.%, thickener 2.0wt.%~5.0wt.%, crystal form regulator 0.1wt.%~1.5wt.%.
[0072] In some embodiments, the mixing process in step S2 includes:
[0073] Step S210, mixing sodium sulfate, inorganic salt B, heterogeneous nucleating agent and crystal form regulator uniformly to obtain mixture A. When the inorganic salt phase change material composition also includes a homogeneous nucleating agent, the homogeneous nucleating agent can be added and mixed uniformly in step S210.
[0074] Step S220: adding deionized water to mixture A, heating to a preset temperature T0, performing a first mixing process, and obtaining a molten mixture B.
[0075] Step S230, adding the thickener to the molten mixture B in multiple times, performing a second mixing process, and obtaining a molten intermediate mixture.
[0076] Among them, step S210 adopts the method of first mixing sodium sulfate, inorganic salt B, heterogeneous nucleating agent and crystal form regulator uniformly, and then adding deionized water in step S220, which helps to evenly disperse the heterogeneous nucleating agent, crystal form regulator, sodium sulfate and inorganic salt B, and prevents the situation that agglomeration occurs when deionized water is added first, which makes it difficult to evenly disperse the components, and further helps these components to be evenly dispersed in subsequent treatment. Step S230 adds thickener in multiple times to facilitate uniform mixing of the thickener, and prevents the thickener from swelling in an environment with water, resulting in uneven dispersion and agglomeration.
[0077] In step S220, the first mixing treatment at least includes: a stirring speed of 50 r / min to 80 r / min, a temperature of 40°C to 75°C, and a time of 1 h to 3 h. In the step of adding deionized water, heating to a preset temperature T0 is performed to melt the deionized water and the mixture A, and the mixture is mixed and emulsified evenly, which helps to disperse the components evenly and form a molten mixture B after the mixture A is mixed with the deionized water.
[0078] In some embodiments, the preset temperature T0 satisfies: 40° C.≤T0≤75° C. Within this temperature range, each component in the inorganic salt phase change material composition can be fully melted.
[0079] Step S230, the second mixing process at least includes: a stirring speed of 20r / min to 60r / min, a temperature of 40°C to 75°C, a time of 2h to 3h, and the weight of the thickener added each time is 1.0% to 2.0% of the total weight of the thickener. The thickener is added in small amounts and multiple times to facilitate the thickener to swell and evenly disperse in the inorganic salt phase change material, so as to better improve the inorganic hydrated salt phase separation and prevent the thickener from agglomerating and causing uneven dispersion when a large amount of thickener is added.
[0080] In step S310, the intermediate mixture is subjected to a cooling treatment to a first temperature T1 to obtain a solidified first mixture, and the cooling treatment at least includes: a cooling rate of 0.5°C / min to 2°C / min, a time of 0.5h to 1.5h, and the intermediate mixture is quickly cooled to the first temperature T1. In some embodiments, 10°C≤T1≤20°C, within this temperature range, the heterogeneous nucleating agent, the homogeneous nucleating agent and the crystal form modifier can be evenly dispersed.
[0081] In step S320, the first mixture is heat-insulated at a first temperature T1 to obtain a second mixture; the heat-insulating treatment at least includes: leaving the first mixture to stand for 3 hours to 8 hours, so that the first mixture can be more fully crystallized to form a second mixture with a higher degree of crystallization and a more uniform crystal phase.
[0082] In step S330, the second mixture is subjected to a temperature increase treatment to a second temperature T2 to obtain a molten third mixture; the temperature increase treatment at least includes: a temperature increase rate of 0.5°C / min to 2°C / min, a time of 0.1h to 1.5h, and the second mixture is quickly heated to the second temperature T2 to form a molten third mixture, so as to further disperse the heterogeneous nucleating agent and the homogeneous nucleating agent evenly. In some embodiments, 40°C ≤ T2 ≤ 75°C, within this temperature range, the heterogeneous nucleating agent and the homogeneous nucleating agent can be further activated, so that the heterogeneous nucleating agent and the homogeneous nucleating agent are more evenly dispersed. In some embodiments, the second temperature T2 may be the phase change temperature T2 of the inorganic salt phase change material. m .
[0083] In step S4, the third mixture is naturally cooled to room temperature, and the third mixture is solidified to form an inorganic salt phase change material. After multiple heating and cooling processes in steps S310, S320, S330 and S4, the present application can make the components in the composition disperse more evenly, and make the components in the obtained inorganic salt phase change material interact with each other, so that the inorganic salt phase change material has a suitable phase change temperature, a lower supercooling degree and a higher thermal enthalpy.
[0084] like Figure 2 As shown, the present application also provides a heat pump system 10, which may include a water heater 100 and an air conditioner indoor unit 400. At least one of the water heater 100 and the air conditioner indoor unit 400 may include an energy storage unit, and the energy storage unit includes an energy storage shell 110, a heat exchange tube 200 and a phase change layer 20, and the phase change layer 20 includes the inorganic salt phase change material as described above. The energy storage shell 110 has an energy storage cavity inside, and the heat exchange tube 200 includes an inlet section, a middle section and an outlet section connected in sequence, the middle section is arranged in the energy storage cavity, and the inlet section and the outlet section extend from the energy storage cavity to the energy storage shell 110. The phase change layer is filled in the energy storage cavity and coated on the middle section of the heat exchange tube 200 to exchange heat with the heat exchange medium in the heat exchange tube 200.
[0085] In some embodiments, the number of heat exchange tubes 200 of the energy storage unit is multiple. Figure 2 As shown, there are two heat exchange tubes 200, one of which is a first heat exchange tube 210 and the other is a second heat exchange tube 220. The heat pump system 10 further includes a heat source unit 300, the inlet section of the first heat exchange tube 210 is connected to the outlet end 310 of the heat source unit 300, and the outlet section is connected to the inlet end 320 of the heat source unit 300, and the heat source unit 300 exchanges heat with the phase change layer 20 through the heat exchange medium in the first heat exchange tube 210.
[0086] When the water heater 100 includes an energy storage unit, the inlet section of the second heat exchange tube 220 of the energy storage unit is connected to the municipal water source 610, and the outlet section is connected to the domestic water pipe 620. The water heater 100 has a heat storage mode, a heat release mode and a mixed mode. Specifically, in the heat storage mode, the high-temperature heat exchange medium of the heat source unit 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and stores the heat. The high-temperature heat exchange medium becomes a low-temperature heat exchange medium and flows back from the outlet section of the first heat exchange tube 210 to the inlet end 320 of the heat source unit 300; in the heat release mode, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section Heat pipe 220, the inorganic salt transfers heat to the low-temperature water flow in the second heat exchange tube 220, and the low-temperature water flow absorbs heat and becomes high-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for supply to users; in the mixed mode, the high-temperature heat exchange medium of the heat source unit 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and at the same time, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section of the second heat exchange tube 220, the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and transfers the heat to the low-temperature water flow in the second heat exchange tube 220 at the same time, the low-temperature water flow absorbs heat and becomes high-temperature water flow or medium-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for supply to users.
[0087] The heat pump system 10 also includes a reversing valve 500 and connecting pipes connecting various structures. The reversing valve 500 includes a first reversing valve 510. The first end of the first reversing valve 510 is connected to the outlet end 310 of the heat source unit 300, the second end is connected to the air-conditioning indoor unit 400, and the third end is connected to the heat exchange pipe 200 of the energy storage unit. By switching the flow path of the first reversing valve 510, the outlet end 310 of the heat source unit 300 can be connected to at least one of the air-conditioning indoor unit 400 and the water heater 100 to provide high-temperature heat exchange medium to the air-conditioning indoor unit 400 and the water heater 100 accordingly. The number of air-conditioning indoor units 400 may be multiple, and the reversing valve 500 may also include a second reversing valve 520. The second reversing valve 520 is arranged on the second end of the first reversing valve 510 and is connected to a connecting pipe connected to the multiple air-conditioning indoor units 400. By switching the flow path of the second reversing valve 520, the second end of the first reversing valve 510 is connected to one or more of the multiple air-conditioning indoor units 400, and then the heat source unit 300 is connected to one or more of the multiple air-conditioning indoor units 400.
[0088] When the air conditioning indoor unit 400 includes an energy storage unit, the second heat exchange tube 220 of the energy storage unit is connected to the atmosphere of the environment in which the air conditioning indoor unit 400 is located. The air conditioning indoor unit 400 has a heating mode and a cooling mode. In the heating mode, the inorganic salt phase change material of the phase change layer of the energy storage unit transfers the stored heat energy to the gas in the second heat exchange tube 220, heats the gas in the second heat exchange tube 220 into hot air and transports it to the environment in which the air conditioning indoor unit 400 is located; in the cooling mode, the inorganic salt phase change material of the phase change layer of the energy storage unit transfers the stored cold energy to the gas in the second heat exchange tube 220, that is, the inorganic salt phase change material absorbs the heat of the gas in the second heat exchange tube 220, cools the gas in the second heat exchange tube 220 into cold air and transports it to the environment in which the air conditioning indoor unit 400 is located. The heat energy and cold energy stored in the inorganic salt phase change material both come from the heat source unit 300.
[0089] The following is a method for preparing an inorganic salt phase change material in combination with an embodiment and a comparative example. It will be understood by those skilled in the art that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. In the following embodiments, unless otherwise specified, all raw materials used are commercially available.
[0090] In each embodiment and comparative example of the present application, the performance test method of the inorganic salt phase change material is as follows:
[0091] 1. Phase change temperature and supercooling test method
[0092] The phase change temperature is measured by the step cooling curve method: 100g of phase change material is placed in a high borosilicate glass bottle, a K-type thermocouple is inserted into the middle of the phase change material, and then the phase change material is heated to 20°C above the melting point of the inorganic salt and stabilized for 30 minutes. Then, it is placed in an environment 30°C below the melting point for natural cooling, and the temperature information of the phase change material changing with time is collected to obtain the temperature-time curve and the corresponding theoretical phase change temperature (T theory ) and the actual phase transition temperature (T actual ).
[0093] The difference between the theoretical phase change temperature and the actual phase change temperature is the supercooling (T sc ).
[0094] 2. Test method for latent heat decay rate of phase change after 2000 cycles
[0095] The initial unit mass phase change latent heat (thermal enthalpy) of the phase change material is measured by DSC equipment.
[0096] The phase change material is loaded into the cycle test device and the melt-crystallization cycle is carried out according to the following steps:
[0097] (1) Initial temperature 0°C, let stand for 5 minutes;
[0098] (2) Perform heating treatment at a heating rate of 5°C / min, a stop temperature of 80°C, and stand for 5 min;
[0099] (3) Cooling treatment was performed at a cooling rate of 5°C / min, an end temperature of 0°C, and the mixture was allowed to stand for 1 min.
[0100] Among them, the above steps (1)-(3) are the first melt-crystallization cycle, and then the steps (2)-(3) are a melt-crystallization cycle. After the phase change material has been melt-crystallized for 2000 times, the unit mass phase change latent heat of the phase change material after 2000 cycles is measured by DSC equipment.
[0101] The calculation formula of the unit mass phase change latent heat decay rate is: H% = (1-△H n / △H0)×100%;
[0102] Among them, △H n is the latent heat per unit mass of phase change material after n cycles, kJ / kg;
[0103] △H0 is the initial unit mass phase change latent heat of the phase change material, kJ / kg.
[0104] 3. Energy storage density test method
[0105] The density of phase change materials was measured by density meter. s ) and liquid density (р l );
[0106] The solid-state specific heat capacity C of phase change materials was measured by differential scanning calorimetry (DSC) using the MDSC method. ps and liquid specific heat C pl .
[0107] The initial unit mass phase change latent heat ΔH0 of the phase change material was measured by differential scanning calorimetry (DSC).
[0108] The energy storage density △Q is calculated according to the following formula:
[0109] △Q=р s ×(T actual -10)×C ps +(р s +р l ) / 2×△H0+р l× (65-T actual )×C pl .
[0110] Example 1-1
[0111] This embodiment provides a method for preparing an inorganic hydrated phase change material, the method comprising the following steps:
[0112] (1) Providing the components of the inorganic hydrated phase change material composition
[0113] Weigh 18.0 g of sodium sulfate, 13.0 g of inorganic salt B sodium carbonate, 4 g of heterogeneous nucleating agent borax pentahydrate, 2 g of crystal form regulator sodium hexametaphosphate, 3.5 g of homogeneous nucleating agent strontium chloride hexahydrate, mix well to obtain mixture A, and weigh 54.5 g of deionized water and 5 g of thickener sodium carboxymethyl cellulose for later use.
[0114] The component contents of the inorganic salt phase change material composition are as follows:
[0115] Sodium sulfate 18.0wt.%, sodium carbonate 13.0wt.%, deionized water 54.5wt.%, borax pentahydrate 4wt.%, sodium carboxymethyl cellulose 5wt.%, sodium hexametaphosphate 2wt.%, strontium chloride hexahydrate 3.5wt.%.
[0116] (2) First mixing process
[0117] All the deionized water was added to the mixture A, heated to a preset temperature T0 = 50°C, and emulsified in an emulsifying device with a stirring speed of 50 r / min for 1.5 h to obtain a molten mixture B.
[0118] (3) Second mixing process
[0119] At 50° C., a thickener, sodium carboxymethyl cellulose, was added to mixture B in 5 portions, with 1 g added each time. The mixture was stirred at a speed of 30 r / min for 3 h to obtain mixture B.
[0120] (4) Cooling treatment
[0121] The mixture B was cooled to a first temperature T1 of 10° C. at a cooling rate of 1° C. / min for 40 min to obtain a first mixture.
[0122] (5) Insulation treatment
[0123] The first mixture was kept at 10°C for 3 hours to obtain a second mixture.
[0124] (6) Heating treatment
[0125] The second mixture was heated to a second temperature T2 of 50° C. at a heating rate of 1° C. / min for 40 min to obtain a third mixture.
[0126] (7) Cooling
[0127] The third mixture is naturally cooled to room temperature, and the third mixture is solidified to form an inorganic salt phase change material.
[0128] Examples 1-2 to 1-10 and Comparative Examples 1-1 to 1-2 are the same as Examples 1-4 except that the contents of sodium sulfate, inorganic salt B, deionized water, heterogeneous nucleating agent, crystal form regulator, homogeneous nucleating agent and thickener are adjusted in each processing step as shown in Table 1.
[0129] Embodiment 1-11 is different from Embodiment 1-1 in that:
[0130] The contents of sodium sulfate, inorganic salt B, deionized water, heterogeneous nucleating agent, crystal form regulator, homogeneous nucleating agent and thickener are adjusted as shown in Table 1, and potassium sulfate is selected as inorganic salt B. In particular, the preset temperature T0 of the first mixing treatment in step (2) is 65°C, and the time is 3h. The cooling rate of the cooling treatment in step (4) is 1°C / min, and the time is 45min, and the temperature is cooled to the first temperature T1 of 20°C. The temperature of the heat preservation treatment in step (5) is 20°C, and the time is 4h. The heating rate of the heating treatment in step (6) is 1°C / min, and the time is 45min, and the temperature is heated to the second temperature T2 of 65°C.
[0131] Embodiment 1-12 is different from Embodiment 1-1 in that:
[0132] The contents of sodium sulfate, inorganic salt B, deionized water, heterogeneous nucleating agent, crystal form regulator, homogeneous nucleating agent and thickener are adjusted as shown in Table 1, and sodium bisulfate is selected as inorganic salt B. In step (2), the preset temperature T0 of the first mixing treatment is 40°C, and the time is 2h. In step (4), the cooling rate of the cooling treatment is 1°C / min, and the time is 30min, and the temperature is cooled to the first temperature T1 of 10°C. In step (5), the temperature of the heat preservation treatment is 10°C, and the time is 3h. In step (6), the heating rate of the heating treatment is 1°C / min, and the time is 30min, and the temperature is heated to the second temperature T2 of 40°C.
[0133] Embodiment 1-13 is different from Embodiment 1-1 in that:
[0134] The contents of sodium sulfate, inorganic salt B, deionized water, heterogeneous nucleating agent, crystal form regulator, homogeneous nucleating agent and thickener are adjusted as shown in Table 1, and ammonium sulfate is selected as inorganic salt B. In step (2), the preset temperature T0 of the first mixing treatment is 45°C, and the time is 2h. In step (4), the cooling rate of the cooling treatment is 1°C / min, and the time is 35min, and the temperature is cooled to the first temperature T1 of 10°C. In step (5), the temperature of the heat preservation treatment is 10°C, and the time is 3h. In step (6), the heating rate of the heating treatment is 1°C / min, and the time is 35min, and the temperature is heated to the second temperature T2 of 45°C.
[0135] Embodiment 1-13 is different from Embodiment 1-1 in that:
[0136] The contents of sodium sulfate, inorganic salt B, deionized water, heterogeneous nucleating agent, crystal form regulator, homogeneous nucleating agent and thickener are adjusted as shown in Table 1, and sodium bisulfate and potassium sulfate are selected as inorganic salt B. In particular, the preset temperature T0 of the first mixing treatment in step (2) is 55°C, and the time is 2h. The cooling rate of the cooling treatment in step (4) is 1°C / min, and the time is 40min, and the temperature is cooled to the first temperature T1 of 15°C. The temperature of the heat preservation treatment in step (5) is 15°C, and the time is 4h. The heating rate of the heating treatment in step (6) is 1°C / min, and the time is 40min, and the temperature is heated to the second temperature T2 of 55°C.
[0137] The differences between Examples 2-1 to 2-11 and Example 1-1 are as follows:
[0138] The component contents of the inorganic salt phase change material composition are: 23.0wt.% sodium sulfate, 17.0wt.% sodium carbonate, 56.0wt.% deionized water, 1.0wt.% borax pentahydrate, 1.5wt.% sodium carboxymethyl cellulose, 0.5wt.% sodium hexametaphosphate, and 1.0wt.% strontium chloride hexahydrate.
[0139] Furthermore, the process parameters in step (2) the first mixing treatment, step (4) the cooling treatment, step (5) the heat preservation treatment and step (6) the heating treatment are different. The specific process parameters are shown in Table 1.
[0140] Comparative Example 2-1 is different from Example 1-1 in that:
[0141] After the second mixing treatment in step (3), step (7) is directly performed to cool to room temperature to obtain an inorganic salt phase change material.
[0142] The preparation parameters and performance parameters of Examples 1-1 to 1-14 and Comparative Examples 1-1 to 1-2 are shown in Table 1.
[0143]
[0144] In Table 1, from Comparative Example 1-1 to Comparative Example 1-2, when the molar ratio of sodium sulfate to inorganic salt B exceeds the range of 0.9 to 1.1, after the inorganic salt phase change material composition is mixed and melted, it is always in a molten state and will not form crystals, which is difficult to meet the use requirements. From Example 1-1 to Example 1-14 in Table 1, it can be seen that by combining sodium sulfate with inorganic salt B in the inorganic salt phase change material composition, and selecting each component of the inorganic salt phase change material composition within a suitable range, the phase change temperature (i.e., solidification temperature) of the obtained inorganic salt phase change material is in the range of 19.5°C to 32.0°C, and the phase change latent heat decay rate, supercooling and 10°C to 65°C energy storage density after 2000 cycles are all within a suitable range, and cold and heat storage can be performed. The inorganic salt phase change material of the embodiment of the present application can be used in a heat pump system and can improve the energy efficiency ratio of the heat pump system.
[0145] The preparation parameters and performance parameters of Examples 2-1 to 2-11 and Comparative Example 2-1 are shown in Table 2.
[0146]
[0147] Comparative Example 2-1 in Table 2 is an inorganic salt phase change material obtained by directly cooling to room temperature after step (3). Although it has a certain initial unit mass of phase change latent heat (i.e., thermal enthalpy value) and energy storage density, it cannot undergo repeated melting-crystallization phase change and is difficult to meet usage requirements.
[0148] It can be seen from Example 2-1 to Example 2-11 in Table 2 that by subjecting the components in the inorganic salt phase change material composition to a first mixing treatment - a cooling treatment - a heat preservation treatment - a heating treatment - a cooling treatment in sequence, the heterogeneous nucleating agent and the homogeneous nucleating agent can be successfully activated, so that the obtained inorganic salt phase change material can be repeatedly melted and crystallized, and the phase change temperature (i.e., the solidification temperature) is in the range of 19.5°C to 32.0°C, and the phase change latent heat decay rate after 2000 cycles, the degree of supercooling and the energy storage density at 10°C to 65°C are all within a suitable range, and can be used in a heat pump system, and can improve the energy efficiency ratio of the heat pump system.
[0149] Figure 3 is the cooling curve of the inorganic salt phase change material obtained in Example 2-1, Figure 4 is the cooling curve of the inorganic salt phase change material obtained in Comparative Example 2-1, from Figure 3 and Figure 4 It can be seen that the step cooling curve of the unactivated inorganic salt phase change material in comparative example 2-1 presents a step-like shape, indicating that the inorganic salt phase change material has not formed a eutectic structure and has poor stability. The supercooling degree of the activated inorganic salt phase change material in example 2-1 is less than 1.5°C, the phase change temperature is between 18.5 and 25°C, and the solidification and melting processes are stable.
[0150] Figure 5 This is the DSC (Diffevential Scanning Calorimetry) test graph of the inorganic salt phase change material obtained in Example 2-1. Figure 6 This is the DSC test graph of the inorganic salt phase change material obtained in Comparative Example 2-1. Figure 5 and Figure 6 It can be seen that the initial unit mass of the unactivated inorganic salt phase change material of comparative example 2-1 is 188.59 J / g, and the initial unit mass of the activated inorganic salt phase change material of example 2-1 is 219.61 J / g. The latent heat of phase change of the unactivated inorganic salt phase change material is 16.44% smaller than that of the activated inorganic salt phase change material. The activated heterogeneous nucleating agent promotes the increase of the degree of crystallization of the inorganic hydrated salt and increases the latent heat of phase change of the inorganic salt phase change material.
[0151] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An inorganic salt phase change material composition, characterized in that: The composition comprises the following components: Phase change substrate 31.wt.%~45.0wt.%, deionized water 50.0wt.%~60.0wt.%, heterogeneous nucleating agent 1.0wt.%~5.0wt.%, thickener 2.0wt.%~5.0wt.%, crystal form regulator 0.1wt.%~3wt.%; Wherein, the phase change substrate comprises sodium sulfate and inorganic salt B, the molar ratio of the sodium sulfate to the inorganic salt B is 0.9-1.1, and the inorganic salt B comprises at least one of carbonates.
2. The composition according to claim 1, characterized in that Based on the total weight of the composition, the composition comprises the following components: Phase change substrate 36wt.%~39wt.%, deionized water 52wt.%~54wt.%, heterogeneous nucleating agent 3wt.%~4wt.%, thickener 2.5wt.%~4.0wt.%, crystal form regulator 0.5wt.%~1.0wt.%.
3. The composition according to claim 1 or 2, characterized in that Based on the total weight of the composition, the weight percentage of the sodium sulfate is 21.5 wt.% to 24 wt.%, and the weight percentage of the inorganic salt B is 13 wt.% to 20 wt.%.
4. The composition according to claim 1, characterized in that The inorganic salt B is selected from at least one of sodium carbonate, calcium carbonate, potassium carbonate, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate.
5. The composition according to claim 1, characterized in that The heterogeneous nucleating agent is selected from at least one of barium sulfate, zeolite, talcum powder and quartz sand; The particle size Dv50 of the heterogeneous nucleating agent ranges from 350 μm to 600 μm.
6. The composition according to claim 1, characterized in that The crystal form regulator is selected from at least one of sodium hexametaphosphate, ammonium sulfate and ethylenediaminetetraacetic acid.
7. The composition according to claim 1, characterized in that The composition further comprises a homogeneous nucleating agent, and the weight percentage of the homogeneous nucleating agent is 1.0 wt.% to 3.0 wt.% based on the total weight of the composition; The homogeneous nucleating agent includes at least one of sodium silicate, sodium metasilicate nonahydrate, sodium metasilicate pentahydrate, and anhydrous borax.
8. The composition according to claim 1, characterized in that The thickener is selected from at least one of sodium polyacrylate, polyvinyl alcohol, carrageenan and sodium carboxymethyl cellulose.
9. An inorganic salt phase change material, characterized in that: The method comprises mixing the components of the inorganic salt phase change material composition according to any one of claims 1 to 8.
10. A heat pump system, characterized in that: An energy storage unit is included, wherein the energy storage unit includes: An energy storage shell having an energy storage cavity therein; A heat exchange tube, disposed in the energy storage chamber; and The phase change layer comprises the inorganic salt phase change material according to claim 9, wherein the phase change layer is filled in the energy storage cavity and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.